2020
DOI: 10.3390/cancers12092716
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Hypothyroidism in Patients with Oropharyngeal Cancer Treated with IMRT: Independent and External Validation of Five Normal Tissue Complication Probability Models

Abstract: We aimed to externally validate five normal tissue complication probability (NTCP) models for radiation-induced hypothyroidism (RIHT) in a prospectively recruited cohort of 108 patients with oropharyngeal cancer (OPC). NTCP scores were calculated using original published formulas. Plasma thyrotropin (TSH) level was additionally assessed in the short-term after RT. After a median of 28 months of follow-up, thirty one (28.7%) patients developed RIHT. Thyroid mean dose and thyroid volume were significant predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…We included non-radiomic patient characteristics in the study, reported models' quality statistics and validated models. Patients were recruited prospectively in 3 clinics for the study by Nowicka et al with the same endpoint of RIHT [7], however radiomic analysis was included in the protocol at the later stage. In the place of validation against "golden standard", that is not established for prediction of RIHT, we compared our models with those by other authors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We included non-radiomic patient characteristics in the study, reported models' quality statistics and validated models. Patients were recruited prospectively in 3 clinics for the study by Nowicka et al with the same endpoint of RIHT [7], however radiomic analysis was included in the protocol at the later stage. In the place of validation against "golden standard", that is not established for prediction of RIHT, we compared our models with those by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid bias, laboratory assessment, contouring, outcome assessments, statistical and radiomic analysis were performed by independent researchers. Details of treatment protocol were described previously [7].…”
Section: Patients and Ct Imagesmentioning
confidence: 99%
See 3 more Smart Citations